Behavioral Control in Belian Traditional Healing Beliefs in Eheng Village West Kutai - Santosa, Aji; Pramono, Joko Sapto; Rahayu, Eka Putri (STIKes Medistra Indonesia, 2025)
Buying traditional medicine is very popular in West Kutai, especially Eheng Village, this is a culture that has been passed down from generation to generation from their ancestors. because this treatment is felt ttreatment and that they do not experience changes in health when undergoing medical treatment, so that people feel that the pain that arises is not a medical disease but rather pain that comes from spirits that live side by side. . Their imagine confabulate invent plan contrive This research uses observation methods and also in-depth interviews. The sampling technique in this research used a purposive sampling technique with 2 main informants and 5 supporting informants. The results of this research used interactive analysis techniques with the help of the Maxqda application. Thus, behavioral control regarding beliefs in Belian treatment is influenced by relatives, family and also customs whose behavior agrees or accepts Belian treatment. It is explained that this treatment has been started since their ancestors and they also believe in it from past to present. So families tend to prefer buying this treatment when they feel that medical treatment is not yet capable of treating them.